2010
DOI: 10.1589/rika.25.41
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Muscle Stiffness and the Relationship between Muscle Stiffness and Pain in Muscle Knots

Abstract: In the first part of the study (S1), we quantified muscle stiffness and gender differences in healthy persons. In the second part (S2), we clarified the relationship between muscle stiffness and pain in myofascial pain syndrome (MPS) which has muscle knots. [Subjects] The subjects of S1 were 52 healthy adults in their twenties. The subjects of S2 were 44 patients complaining of chronic lumbago, who showed no imaging or neurological findings and had muscle knots in the longissimus thoracis. [Methods] In S1, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Neutone, which can be calibrated by using the formula N = 0.0258 × repulsion force value + 0.4, is a portable device that can measure muscle hardness over a range of 1 to 100 repulsive force values by slowly pressing the target muscle vertically in a relaxed posture. [ 19 ] The intra-examiner reliability of Neutone ranged from 0.94 to 0.98. [ 20 ]…”
Section: Methodsmentioning
confidence: 99%
“…Neutone, which can be calibrated by using the formula N = 0.0258 × repulsion force value + 0.4, is a portable device that can measure muscle hardness over a range of 1 to 100 repulsive force values by slowly pressing the target muscle vertically in a relaxed posture. [ 19 ] The intra-examiner reliability of Neutone ranged from 0.94 to 0.98. [ 20 ]…”
Section: Methodsmentioning
confidence: 99%
“…They found that there was no strong correlation. However, muscle pain can be caused by hypertonic muscle and induration of muscle for an extended period of time [ 8 ]. Therefore, it is possible that there is no pain even if the muscle is hypertonic condition if the condition does not last long enough.…”
Section: Discussionmentioning
confidence: 99%